(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to build an educational unit designed according to the expanded learning model in the communication and informatics subject prescribed in the Art Education Department, and to know the size of the effect. The researchers chose the research sample in a random manner and it consisted of (54) male and female students of the fourth stage distributed between two classrooms, the hall (1) represented the experimental group, with (27) students, and the hall (3) represented the control group, with (27) Male and female students, the researchers adopted the experimental design with partial control for two groups (experimental and control) with pre and post tests. It includes six study plans, and the pre-achievement test is the same as the post-test, consisting of (30) paragraphs of the multiple-choice type with four alternatives The validity and reliability were verified, the difficulty factor was calculated, the discriminatory power, and the effectiveness of the wrong alternatives to the test. After completing the correction, use the t-test and the U2 Eta square In order to verify the significance of the differences between the two groups and the results showed, the researcher reached the superiority of the experimental group that studied the unit according to the expanded learning model over the control group that studied in the usual way.